Demodex folliculorum - Ayyad Zartasht Khan; Fredrik Fineide; Jens Wohlmann; Kjell Gunnar Gundersen; Morten Gundersen; Miriam Kolko; Tor Paaske Utheim (Diagnostics)
Herein, we present scanning electron microscopy imagery of Demodex folliculorum on the eyelashes of a patient with a two-year history of dry, burning, and watery eyes. Demodex mites are part of the normal human skin flora, inhabiting hair follicles and sebaceous glands. However, in some individuals, they may contribute to ocular surface diseases, including blepharitis and dry eye disease. Symptoms often include itching, photophobia, and a foreign body sensation. The pathogenic role of Demodex is not fully understood but may involve microabrasions, gland obstruction, hypersensitivity reactions, and bacterial dysbiosis. The presence of collarettes at the base of eyelashes is a diagnostic hallmark. Although optimal treatment remains debated, options include topical tea tree oil, ivermectin, and a recently FDA-approved drug lotilaner. Our patient responded favorably to a two-month regimen of tea tree oil-based eyelid wipes. This case underscores the clinical relevance of Demodex infestation in chronic ocular discomfort and highlights the importance of diagnostics.